Fetal cardiac magnetic resonance imaging of the descending aorta in suspected left-sided cardiac obstructions - Fricke, Katrin; Ryd, Daniel; Weismann, Constance G.; Hanséus, Katarina; Hedström, Erik; Liuba, Petru (Frontiers in Cardiovascular Medicine, 2023)
Background: Severe left-sided cardiac obstructions are associated with high morbidity and mortality if not detected in time. The correct prenatal diagnosis of coarctation of the aorta (CoA) is difficult. Fetal cardiac magnetic resonance (CMR) may improve the prenatal diagnosis of complex congenital heart defects. Flow measurements in the ascending aorta could aid in predicting postnatal CoA but its accurate visualization is challenging. Objectives: to compare the flow in the descending aorta (DAo) and umbilical vein (UV) in fetuses with suspected left-sided cardiac obstructions with and without the need for postnatal intervention and healthy controls by fetal phase-contrast CMR flow. A second objective was to determine if adding fetal CMR to echocardiography (echo) improves the fetal CoA diagnosis. Methods: Prospective fetal CMR phase-contrast flow in the DAo and UV and echo studies were conducted between 2017 and 2022. Results: Forty-six fetuses with suspected left-sided cardiac obstructions (11 HLHS, 5 critical aortic stenosis (cAS) and 30 CoA) and five controls were included. Neonatal interventions for left-sided cardiac obstructions (n=23) or comfort care (n=1 HLHS) were pursued in all 16 fetuses with suspected HLHS or cAS and in 8 (27%) fetuses with true CoA. DAo or UV flow was not different in fetuses with and without need of intervention. However, DAo and UV flows were lower in fetuses with either retrograde isthmic systolic flow (DAo flow 253 (72) vs 261 (97) ml/kg/min, p=0.035; UV flow 113 (75) vs 161 (81) ml/kg/min, p=0.04) or those with suspected CoA and restrictive atrial septum (DAo flow 200 (71) vs 268 (94) ml/kg/min, p=0.04; UV flow 89 vs 159 (76) ml/kg/min, p=0.04) and those without these changes. Adding fetal CMR to fetal echo predictors for postnatal CoA did not improve the diagnosis of CoA. Conclusion: Fetal CMR-derived DAo and UV flow measurements do not improve the prenatal diagnosis of left-sided cardiac obstructions, but could be important in identifying fetuses with a more severe decrease in blood flow across the left side of the heart. The physiological explanation may be a markedly decreased left ventricular cardiac output with subsequent retrograde systolic isthmic flow and decreased total DAo flow.